Digital Skills For Future Career: Penguatan Pemasaran Digital Profesional Bagi Mahasiswa - Lati Sari Dewi; Fitriani; Adi Robith Setiana; Risman Barkah; Erna Maulida (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This Community Service Program (PKM) aims to enhance the knowledge, understanding, and skills of students majoring in marketing in the field of digital marketing as a crucial competency in the digital economy era. Although students are accustomed to using digital media and social media, its utilization as a professional marketing tool remains suboptimal. The PKM activities were carried out through structured training covering fundamental concepts of digital marketing, the use of social media for marketing purposes, Search Engine Optimization (SEO), Search Engine Marketing (SEM), and content-based marketing strategies. The training was implemented through material presentations and interactive discussions to encourage active student participation. The results indicate that students experienced an improvement in their understanding and skills in applying digital marketing strategies in a more directed and professional manner, particularly in social media management and search engine optimization. This program provides direct benefits to students and supports institutional efforts to prepare adaptive graduates who are ready to meet the demands of the digital-based industry.